Towards an iconic decision support system for traditional medical practitioners - (:unkn) unknown (My University, 2016)
«Setting up a social and semantic web framework for knowledges sharing in West African communauties» is a project in which we note an important section relating to traditional medicine practitioner (TMP). People TMP, for the most part, are illiterate. Make available, a tool which transcends this characterization, constitutes a scientific issue in this work. Thus, the visual aspect via an iconic composition based on ontological approach of ontoMEDTRAD, is our goal. ontoMEDTRAD includes two modules which are ontoConcept_term and ontoIcone. It is also a part of the management system for traditional medicine (sysMEDTRAD). ontoConcept_term denotes the terms of concepts in this domain. ontoIcone will include the set of icons corresponding or in alignment with those terms.
Keywords: African Research